"استخدامات الطلبة الجامعيين للبرامج التلفزيونية ( الكاميرا الخفية ) و الاشباعات المتحققة - بوعروة ، حياة, حضري، محمود (جامعة الوادي University of eloued, 2018)
"ملخص الدراسة: تهدف هذه الدراسة الى التعرف على استخدامات الطلبة الجامعيين لكلية العلوم الاجتماعية والانسانية للبرامج التلفزيونية (الكاميرا الخفية) للاشباعات المتحققة, من خلال الاجابة على تساؤلات الدراسة التالية: - ماهي عادات وانماط مشاهدة الطلبة الجامعيين لبرامج الكاميرا الخفية ؟ - ماهي دوافع مشاهدة الطلبة الجامعيين لبرامج الكاميرا الخفية ؟ - ماهي الاشباعات المتحققة من مشاهدة الطلبة الجامعيين لبرامج الكاميرا الخفية؟ ولقد اعتمدت الدراسة على المنهج المسحي الوصفي معتمدين على اداة استبيان لجمع البيانات والملاحظة المباشرة، حيث وزع هذا الاستبيان على 200 مفردة من مجتمع الدراسة باسلوب العينة الطبقية ذات التوزيع المتناسب فيما استرد منها 199 استمارة. وقد توصلت الدراسة إلى عدة نتائج أهمها: - أغلب عادات وانماط مشاهدة طلبة العلوم الاجتماعية والانسانية لبرامج الكاميرا الخفية تستحق المشاهدة على القنوات العربية خاصة ومع العائلة في اوقات متباينة. - أهم دوافع مشاهدة الطلبة الجامعيين لبرامج الكاميرا الخفية هو الفراغ مما يولد ردود افعال ايجابية عند متابعتهم لها. - إن الاشباعات التي تحققها الكاميرا الخفية من مشاهدة الطلبة الجامعيين للعلوم الاجتماعية والانسانية هي اشباعات اجتماعية، نفسية ومعرفية. " "Abstract: The purpose of this study is to identify the uses of university students of the social and human sciences faculty for television programs (hidden camera) for the realized rumors, by answering the following study questions: - What are the habits and patterns of watching university students of hidden camera programs? - What are the motives of watching university students for hidden camera programs? - What are the expectations of watching university students for hidden camera programs? The study was based on a descriptive descriptive approach, based on a questionnaire tool for data collection and direct observation. The questionnaire was distributed to 200 members of the study population in a proportionally distributed stratified sample with 199 responses retrieved. The study reached several results, the most important of which are: - Most habits and patterns of watching students of social and human sciences for hidden camera programs are worth watching on Arab channels, especially with the family at different times. - The most important motivations for students watching the programs of the hidden camera is the vacuum, which generates positive reactions when they follow them. - The latencies achieved by the hidden camera from the observation of university students of social and human sciences are social, psychological and cognitive."
مذكرة ماستر في الإعلام والإتصال تخصص السمعي البصري
Keywords: الاستخدامات – طلبة العلوم الاجتماعية والانسانية, الكاميرا الخفية; Pour usages - étudiants en sciences sociales et humaines, caméra cachée; For uses - students of social and human sciences, hidden camera